2019
DOI: 10.12669/pjms.35.2.644
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and impacts heavy menstrual bleeding on anemia, fatigue and quality of life in women of reproductive age

Abstract: Objectives: To investigate the prevalence and impacts of heavy menstrual bleeding (HMB) on anemia, fatigue, and the quality of life (QoL) in women of reproductive age. Methods: This study was conducted among 306 women of reproductive age who presented at the internal medicine outpatient departments of the training and research hospital of a university. The data of the study were collected by the “Data collection form”, “SF-36 Quality of Life Scale (SF-36 QoLS)” and “Brief Fatigue Inventory (BFI)”. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 19 publications
(52 reference statements)
2
43
1
7
Order By: Relevance
“…Subjects W1 and W3 were two of four women who reported heavy menstrual bleeding. The percentage of women experienced heavy bleeding (24%) in our study is in agreement with the findings of Fraser and colleagues who in a general female population found that 27% of their respondents reported heavy menstrual bleeding, 35 but not others who find 3% 18 and 38%, 36 whereas in elite athletes 13% 18 and 37% 17 reported heavy bleedings. A blood loss above 80 mL has been associated with lower HGB concentrations.…”
Section: Intra-individual Variationsupporting
confidence: 92%
“…Subjects W1 and W3 were two of four women who reported heavy menstrual bleeding. The percentage of women experienced heavy bleeding (24%) in our study is in agreement with the findings of Fraser and colleagues who in a general female population found that 27% of their respondents reported heavy menstrual bleeding, 35 but not others who find 3% 18 and 38%, 36 whereas in elite athletes 13% 18 and 37% 17 reported heavy bleedings. A blood loss above 80 mL has been associated with lower HGB concentrations.…”
Section: Intra-individual Variationsupporting
confidence: 92%
“…Interestingly, we did not find any correlation between heavy menstrual bleeding and anaemia, but given the higher risk of fatigue-related symptoms in those reporting heavy menstrual bleeding, athletes and coaches should be aware of the increased iron needs in women who may have more frequent or heavier periods. 26…”
Section: Discussionmentioning
confidence: 99%
“…The UK-based National Institute for Health and Care Excellence (NICE) has therefore suggested that HMB should also be diagnosed when there is regularly excessive menstrual blood loss that ''affects the physical, social, emotional or material quality of life of the patient'' [4,5]. HMB is estimated to affect approximately 18-38% of women of reproductive age and may increase in prevalence for women approaching menopause [6][7][8][9][10][11][12]. However, there is considerable variability in the reporting of HMB, and the condition is likely to be underdiagnosed [6,13].…”
Section: Introductionmentioning
confidence: 99%